Inequalities in healthy behaviors during the COVID-19 pandemic in children from public and private schools of Buenos Aires - De Roia, Gabriela Fernanda (2025)
Objective: To compare physical activity (PA), screen time (ST), and sleep behaviors before and during the mandatory preventive social isolation (ASPO, for its acronym in Spanish) due to COVID-19 among children attending public and private primary schools in the Greater Buenos Aires metropolitan area. Methods: A total of 379 adult caregivers of children attending public and private primary schools completed an online survey on PA, ST, and sleep behaviors before and during ASPO. School type was used as an indicator of socioeconomic status, with private schools’ students considered more privileged than public schools’ students. Results: For both groups, ASPO resulted in a reduction in PA (-43%) and an increase in ST (79.9%). Children attending private schools had the worst results, since they started with better behaviors (PA pre vs during: 3.5 ± 1.3 vs 1.9 ± 2.0 days/week; ST pre vs during: 2.1 ± 0.6 vs 3.8 ± 1.0 days/week) compared to the children attending public schools (PA pre vs during: 3.1 ± 1.8 vs 1.8 ± 1.5 days/week; ST pre vs during: 2.4 ± 0.9 vs 3.6 ± 1.3 days/week). Sleep increased by 7.6% with a shift towards later bed and wake-up times, with public schools’ students being more affected. Conclusion: ASPO restrictions led to unfavorable changes in PA, ST and sleep behaviors among children attending public schools and private schools. ASPO evened out the pre-pandemic differences between public schools and private schools’ students in PA and ST behaviors.